Pengaruh Media E-Learning Terhadap Minat Belajar Mahasiswa Prodi Pendidikan Akuntansi Universitas Negeri Makassar - Hasnira, Hasnira; Tikollah, M. Ridwan; Nuraisyiah, Nuraisyiah (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the influence of e-learning media on the learning interest of accounting education students at Makassar State University. The variables in this study are e-learning media (X) and learning interest (Y) which are measured using a Likert scale. The population in this study is students of the Accounting Education Program at Makassar State University. The data collection technique in this research uses questionnaires and documentation. The data analysis techniques used are descriptive analysis, simple linear regression analysis, instrument testing, and hypothesis testing. Based on the data analysis, a simple linear regression equation was obtained: Y = 26.171 + 0.480X, which means that if the e-learning media variable is considered to be zero, the interest in learning variable is 26.171. From the results, the coefficient of determination r2 is 0.120, which means that e-learning media accounts for 12.0% of the influence on interest in learning, while the remaining is influenced by other factors not studied. Furthermore, the effect of e-learning media on interest in learning is indicated by a significance value of 0.000, which is less than 0.05 (0.000 < 0.05), meaning the hypothesis of a positive effect of e-learning media on the interest in learning of students in the Accounting Education Program is accepted.